Bisnis Waralaba Bidang Pendidikan Ditinjau Dari Perspektif Tri Hita Karana: Studi Literasi - I Gusti Agung Ayu Wulandari; I Nengah Suastika (Cetta: Jurnal Ilmu Pendidikan, 2022)
This research is a literature study with a descriptive qualitative research type with library research which seeks to describe the franchise business in the field of education in terms of the perspective of Tri Hita Karana. In this literature study the author uses various written sources such as articles, journals and documents relevant to the study in this study. This study focuses on the description of the franchise business in the field of Education (Primagama, Kumon, Bimba Aiueo, And Go) and how it is applied in the perspective of Tri Hita Karana. The results of the study show that tutoring such as Ganesha Operation, Primagama, Bimba Aiueo, and Kumon have been developed based on Tri Hita Karana both explicitly and implicitly and not only concerned with profit. The form of franchise development in education based on Tri Hita Karana includes continuing to try to develop their franchise by continuing to believe in god (parahyangan), behaving well to students and workers (pawongan), and finally using electronic media to replace paper that will be used. impact on the environment (palemahan).